Síntese e desempenho da lignina catiônica como floculante para o tratamento de águas residuárias - Tejada, Luma Schervenski (2022)
The largest source of lignin currently available is the residue from the pulp/paper manufacturing process. Kraft lignins are weakly anionic, low molecular weight polymers of limited utility without modification. Cationic lignin has advantages that reside in its wide range of applications, and can be used in the treatment of effluents. Derivatization is a usual strategy to improve its surfactant property. Organic polymers of plant origin represent an important alternative for replacement or use in conjunction with conventional coagulants/flocculants. In this study, lignin was purified from black liquor, as well as lignin extraction from Pinus taeda and Eucalyptus grandis woods using the Klason method. The derivatization process for cationization was carried out with 3-chloro-2-hydroxypropyltrimethylammonium chloride in a pH 12 medium, under stirring for 1.5 hours at a temperature of 60ºC. Purification of the solid reaction product was carried out after pH neutralization, washing with water and vacuum filtration. The degree of substitution (DS) that occurred by the grafting of quaternary ammonium groups on lignin monomers was characterized, as well as the DS by the chloride content. Subsequently, the performance of the synthesized polymers as flocculants for the treatment of leached effluent from a sanitary landfill was evaluated. The kraft and Klason lignins from Pinus taeda and Eucalypitus grandis showed satisfactory DS in relation to the nitrogen graft in the samples, in the order of 0.31; 0.31 and 0.34, respectively. The DS calculated as a function of the chloride content proved to be an indicator of low precision and experimental reliability for the method used. The landfill leachate was characterized as recent, with high color, medium metal content and important biodegradability. The lignins cationized from Pinus taeda and Eucalypitus grandis showed low potential for color removal after cationization, in addition to providing turbidity to the effluent. For the conditions of this study, aluminum sulfate, Tanfloc SG and Lignin kraft cationic (LKC), in that order, showed the best performances. The best dosages followed by the percentages of color removal and turbidity, respectively, were: aluminum sulfate 1000 mg.L1 , 95% and 94%; Tanfloc SG 1000 mg.L-1 , 83% and 81% and LKC 640 mg.L-1 , 50% and 70%. LKC proved to be a promising organic flocculant for the treatment of wastewater.